SIMULASI NUMERIK PENGARUH DIAMETER DAN KECEPATAN ALIRAN TERHADAP PERFORMANSI SINGLE SERPENTINE CHANNEL PADA PV - Gunawan, I Gede Nengah Wika; Suryawan, Anak Agung Adhi; Astawa, Ketut; Rasmini, Ni Wayan (Machine : Jurnal Teknik Mesin, 2024)
The application of photovoltaic energy (PV) is currently very massive due to the savings and implementation of new and renewable energy. In the use of PV, an increase in temperature affects the optically generated electrical power. One way to reduce the PV temperature is by optimizing the design of the cooling channel. The method used in this research is a three-factor factorial design where the variable that is set is a diameter of 1.5 inches; 2 inches; and 2.5 inches and an inlet flow rate of 0.5 ; 0.6 ; and 0.7 , using CFD along with analytical calculations. The results showed that the 2.5 inch diameter configuration with a speed of 0.7 m/s produced an average temperature of 30.188 ℃ while the 1.5 inch configuration with a speed of 0.5 m/s produced an average temperature of 36.664℃. The temperature becomes lower with the larger pipe diameter configuration and the use of higher fluid velocity